2021
DOI: 10.1111/1755-0998.13382
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome‐level genome assembly of burbot (Lota lota) provides insights into the evolutionary adaptations in freshwater

Abstract: Gadiformes includes some of the most important commercial fish (e.g., cod, hake, and haddock) worldwide and accounts for approximately 18% of the world's total marine fish catch (FAO, 2004).Gadiform fish inhabit cold waters in every high-latitude oceans from deep-sea benthic habitats to coastal waters. Only one species in this order, that is, the burbot (Lota lota), is in freshwater habitats (Nelson, 1994). However, to date, the only available high-quality genome sequences of the Gadiformes species are for Atl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…The final genome assembly was 583.78 Mb, with a contig N50 of 9.08 Mb, and a scaffold N50 of 21.89 Mb ( Table 1 ). In comparison with a recently released burbot genome assembly by Han et al (2021) , it was suggested that the genome assembled in this study has better quality for higher contig N50 and more accurate chromosome number ( Supplementary Table 4 ). The contig N50 of the genome assembled by Han et al (2021) was 2.01 Mb, and the assembled sequences were anchored to 22 pseudochromosomes, which might be attributed to a low resolution of Hi-C assembly or chromosome loss or fusion caused by local adaptation.…”
Section: Datamentioning
confidence: 86%
See 1 more Smart Citation
“…The final genome assembly was 583.78 Mb, with a contig N50 of 9.08 Mb, and a scaffold N50 of 21.89 Mb ( Table 1 ). In comparison with a recently released burbot genome assembly by Han et al (2021) , it was suggested that the genome assembled in this study has better quality for higher contig N50 and more accurate chromosome number ( Supplementary Table 4 ). The contig N50 of the genome assembled by Han et al (2021) was 2.01 Mb, and the assembled sequences were anchored to 22 pseudochromosomes, which might be attributed to a low resolution of Hi-C assembly or chromosome loss or fusion caused by local adaptation.…”
Section: Datamentioning
confidence: 86%
“…In comparison with a recently released burbot genome assembly by Han et al (2021) , it was suggested that the genome assembled in this study has better quality for higher contig N50 and more accurate chromosome number ( Supplementary Table 4 ). The contig N50 of the genome assembled by Han et al (2021) was 2.01 Mb, and the assembled sequences were anchored to 22 pseudochromosomes, which might be attributed to a low resolution of Hi-C assembly or chromosome loss or fusion caused by local adaptation. A total length of 537.89 Mb of the genomic sequence was anchored, accounting for 92.1% of the entire assembly ( Supplementary Table 5 ).…”
Section: Datamentioning
confidence: 86%
“…Genomic and transcriptomic data for 40 species representing 8 gadiform families and 2 outgroup species (i.e., Cyttopsis rosea and Zeus faber) from the order Zeiformes were retrieved from the NCBI database (Table 1). A new genome assembly of L. lota from Amur River, China was included in this study [29].…”
Section: Genomic and Transcriptomic Data Set Collectionmentioning
confidence: 99%
“… 29–31 Chromosome-level genomes have also been reported in catfishes, such as channel catfish ( Ictalurus punctatus ), 32 yellow catfish ( Pelteobagrus fulvidraco ), 33 giant devil catfish ( Bagarius yarrelli ), 34 Southern catfish ( Silurus meridionalis ), 35 Chinese longsnout catfish ( Leiocassis longirostris ), 36 striped catfish ( Pangasianodon hypophthalmus ), 37 and redtail catfish ( Hemibagrus wyckioides ). 38 These chromosome-level assemblies have been widely used as reliable reference genomes for studies of many fields, including ecological adaptation, 35 , 39 , 40 genome evolution, 41–43 gene evolution, 44 , 45 immunology, 46–48 and identification of target-trait-related genes, 49 , 50 in aquatic animals. Moreover, chromosome-level genomes have also been used for studies on sex determination mechanisms, including identification of sex determination regions and genes, 51–53 sex reversal, 54 , 55 and sex chromosome evolutions.…”
Section: Introductionmentioning
confidence: 99%